The Relationship Between Corporate Tax Rate and Economic Growth During the Global Financial Crisis: Evidence from a Panel VAR - Gamze Oz̈ Yalaman (European Journal of Government and Economics (EJGE), 2019)
This paper compares dynamic relationship between economic growth and corporate tax rate during the recent financial crisis and the non-crisis period using a panel VAR for 29 OECD countries over the period 1998-2016. The results show that corporate tax rate has a significantly negative effect on economic growth. Moreover, the recent financial crisis has had a significant effect on the endogenous interaction between corporate tax rate and economic growth. According to Granger causality test, there is only one-way causality from corporate tax rate to economic growth during the non-crisis period. Interestingly, there are not any causal relationships between corporate tax rate and economic growth during the crisis period. The results show that the recent crisis has had a significant effect on the endogenous interaction between corporate tax rate and economic growth.
Keywords: H25; F23; 330; corporate tax; OECD countries; panel VAR